Diagnosis and Treatment of Autoimmune Hepatitis: Questions, Answers, and Illustrative Cases: Endorsed by Autoimmune Liver Diseases Special Interest Group, Turkish Association for the Study of Liver - Özaslan, Ersan; Günşar, Fulya; Çiftçibaşı Örmeci, Aslı; Hatemi, İbrahim and Efe, Cumali and Akyol, Gülen and Turhan, Nesrin and Yılmaz Barbet, Funda and Sağol, Özgül and Ataizi Çelikel, Çiğdem and et al. (Turkish Journal of Gastroenterology, 2023)
Autoimmune hepatitis (AIH) is a rare, immune-mediated liver disease. It has a heterogeneous nature with varied clinical presentations. The management of patients with AIH is challenging in many ways. The main difficulties are inexperience due to the rarity of the disease, diagnostic confusion in controversial areas such as variant/overlap cases, acute presentations, the presence of non-alcoholic fatty liver disease or drug-induced liver injury features, and the long and complex course of treatment. Here, we provide a clear, concise, and visualized review regarding the diagnosis and treatment of AIH, including illustrative cases.